Control of human trophoblast function - Biondi Carla; Medici Silvia; Ferretti Maria E; Lunghi Laura; Vesce Fortunato (BMC, 2007)
Abstract The trophoblast, i.e. the peripheral part of the human conceptus, exerts a crucial role in implantation and placentation. Both processes properly occur as a consequence of an intimate dialogue between fetal and maternal tissues, fulfilled by membrane ligands and receptors, as well as by hormone and local factor release. During blastocyst implantation, generation of distinct trophoblast cell types begins, namely the villous and the extravillous trophoblast, the former of which is devoted to fetal-maternal exchanges and the latter binds the placental body to the uterine wall. Physiological placentation is characterized by the invasion of the uterine spiral arteries by extravillous trophoblast cells arising from anchoring villi. Due to this invasion, the arterial structure is replaced by amorphous fibrinoid material and endovascular trophoblastic cells. This transformation establishes a low-resistance, high-capacity perfusion system from the radial arteries to the intervillous space, in which the villous tree is embedded. The physiology of pregnancy depends upon the orderly progress of structural and functional changes of villous and extravillous trophoblast, whereas a derangement of such processes can lead to different types of complications of varying degrees of gravity, including possible pregnancy loss and maternal life-threatening diseases. In this review we describe the mechanisms which regulate trophoblast differentiation, proliferation, migration and invasiveness, and the alterations in these mechanisms which lead to pathological conditions. Furthermore, based on the growing evidence that proper inflammatory changes and oxidative balance are needed for successful gestation, we explain the mechanisms by which agents able to influence such processes may be useful in the prevention and treatment of pregnancy disorders.